2010
DOI: 10.1016/j.jacc.2010.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Intra-Atrial Re-Entrant Tachycardia Catheter Ablation in Adults With Congenital Heart Disease

Abstract: In adults with CHD, acute and long-term outcomes of RFCA for IART are similar to those reported for younger cohorts. Complex atrial surgery limits the success of RFCA, and older age is associated with a higher risk of IART recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
99
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 26 publications
9
99
0
Order By: Relevance
“…Catheter ablation is an effective therapy for arrhythmia recurrent in patients with CHD. 16 Ammash et al 6 reported that 60% of the CHD group had arrhythmia recurrence within 18 months after DCCV, a recurrence rate comparable with that for the non-CHD group in that study. The risk factors for arrhythmia recurrence were atrial fibrillation and spontaneous echocardiographic contrast.…”
Section: Discussionmentioning
confidence: 51%
“…Catheter ablation is an effective therapy for arrhythmia recurrent in patients with CHD. 16 Ammash et al 6 reported that 60% of the CHD group had arrhythmia recurrence within 18 months after DCCV, a recurrence rate comparable with that for the non-CHD group in that study. The risk factors for arrhythmia recurrence were atrial fibrillation and spontaneous echocardiographic contrast.…”
Section: Discussionmentioning
confidence: 51%
“…In a recent study that reported ablation outcomes in 19 patients after the Fontan procedure, only 3 (15%) patients were free from arrhythmia recurrence at 4 years of follow-up [22]. These results are clearly worse compared to patients with other CHD, both simple and complex [22].…”
Section: Discussionmentioning
confidence: 97%
“…Literature data indicate that short-term efficacy of ablation in patients after the Fontan procedure is 43-83%, and the recurrence rate during long-term follow-up (up to 4 years) is 32-76% [10,[20][21][22]. In a recent study that reported ablation outcomes in 19 patients after the Fontan procedure, only 3 (15%) patients were free from arrhythmia recurrence at 4 years of follow-up [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidence of late arrhythmias in patients with modified connections can be expected to rise with longer follow-up. Catheter ablation in the Fontan patient has acute success rates of about 50% with at least 70% recurrence of tachycardia within two years (37,38). Catheter access to the right atrium in patients with extracardiac connections is limited to the transhepatic or transthoracic approach with potential morbidity.…”
Section: Arrhythmias and Congenital Heart Diseasementioning
confidence: 99%